Application of Pregnant Mom's Diet Based on Raspberry PI Using Telegram Chatbot - Yuli Wahyuni; Fariz Ammar; Irma Anggraeni (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
A healthy and regular diet is needed to maintain the body's immunity, the benefits that can be used for mothers and fetuses to help in the growth and development of the fetus in the mother's womb so that the eating patterns that are consumed must have good quality and nutrition, because good diet can be increase the development of the fetus while in the womb, so it is necessary to make an application with the aim of providing information on a dietary pattern of raspberry-based pregnant women using the telegram chatbot. In this study using the Software Development Life Cycle (SDLC) method where this method has a plan in the form of planning, analysis (analysis), design (design), implementation (implements) and management (maintenance). The results of this study use the telegram chatbot as a medium of information that can be delivered easily because the working principle of the chatbot on the telegram has a button feature that makes it easier for user friendly-based use so as to reduce the system error. Users will get results in the form of a PDF document (information on diet, nutritional content, and examples of foods that can be consumed) or images of good solutions and nutrition so that they can be downloaded easily through mobile phones with a minimum specification in the form of Android and Notebook and Personal Computer (PC).